Supplier Assessment and Order Allocation Determination for Fast Moving Consumer Goods - Roni Sahroni, Taufik; Ivander, Ivander (International Journal of Supply Chain Management, 2017)
Supply chain management in manufacturing has been widely discussed by researchers and industrial engineers due to complexity of activities. One of the supply chain activities is supplier selection.  Supplier selection has involved in maintaining the smoothness of process production, the dependency between suppliers has becomes a serious concern for company. This study focuses on the supplier selection problem to obtain the best supplier for Fast Moving Consumer Goods (FMCG) Company. The criteria of supplier selections for (FMCG) company were introduced.  The criteria in supplier evaluations are limited to quality, price, payment term, quantity accuracy, on time accuracy, response of supplier, flexibility of supplier and completeness of document. The weights of importance level for each criteria is processed by using Analytic Hierarchy Process (AHP) approach. In obtaining information on supplier overall performance, the weights of importance level is multiplied with actual supplier score. As the result, the score of overall supplier performance could help decision maker in deciding the amount of allocation order that should be distributed for each supplier.